Tinjauan Hukum Islam Terhadap Mustahik Zakat Gharimin di Desa Tanjung Baringin Kecamatan Hutaraja Tinggi Kabupaten Padang Lawas - Ismail Nasution; Romi Saputra Al-Amin Hasibuan; Mahmudin Hasibuan (Indo Publishing, 2025)
This study aims to determine the criteria for gharimin as mustahik zakat according to Islamic law and the Islamic legal review of mustahik zakat gharimin in Tanjung Baringin Village, Hutaraja Tinggi District, Padang Lawas Regency. The type of research used is field research with a qualitative descriptive method, which attempts to comprehensively describe the social conditions related to gharimin. The research subjects include the community of Tanjung Baringin Village, while the research object is mustahik zakat gharimin. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the criteria for gharimin as mustahik zakat according to Islamic law are people who have debts due to the necessities of life or the interests of defending truth and justice, but not debts used for crime or immorality. This is in line with the opinions of four schools of thought, namely Hanafi, Maliki, Syafi'i, and Hambali. A review of Islamic law regarding those entitled to gharimin zakat in Tanjung Baringin Village shows that all six respondents interviewed are classified as mustahik zakat gharimin because they are poor individuals who have debts for purposes that do not violate Islamic law. Therefore, the distribution of zakat to them is valid and in accordance with Islamic law.